Team-based learning in the biblical studies classroom: Utilizing the 4S application task to promote deep learning - Flanders, Denise C. (2023)
This article provides a brief overview of the instructional strategy known as team-based learning (TBL). It then focuses specifically on the use of one of its integral components in a biblical studies classroom—namely, the “4S application task.” The 4S application task, which is one of the fundamental pieces of the learning experience in TBL, consists of the problems that small group teams of students need to solve or the decisions the teams need to reach in each class session. The title 4S refers to the fact that the problems must be characterized by the following: significant problem, same problem, specific choice, and simultaneous report. The main aim of this article is to share this engaging and generative pedagogical activity, but to do so effectively by providing some context as to how it is situated within the overarching flow and goals of a TBL approach.
Keywords: team-based learning; Problem-based Learning; Group Work; deep learning; Biblical Studies; active learning